2021
DOI: 10.1002/jper.21-0277
|View full text |Cite
|
Sign up to set email alerts
|

The “oral” history of COVID‐19: Primary infection, salivary transmission, and post‐acute implications

Abstract: Severe acute respiratorysyndrome coronavirus 2 (SARS-CoV-2), the causative agent of COVID-19, has led to more than 3.25 million recorded deaths worldwide as of May 2021. COVID-19 is known to be clinically heterogeneous, and whether the reported oral signs and symptoms in COVID-19 are related to the direct infection of oral tissues has remained unknown. Here, we review and summarize the evidence for the primary infection of the glands, oral mucosae, and saliva by SARS-CoV-2. Not only were the entry factors for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 58 publications
(107 reference statements)
1
16
0
2
Order By: Relevance
“…Recent studies suggest that sex hormones may influence the viral infectivity process ( Mohamed, Moulin, & Schiöth, 2021 ). However, the pathophysiology of this difference has not yet been established and it was observed that genes encoding entry factors for SARS-CoV-2 appeared similar in epithelial cells from males and females (Huang, P é rez, Kato, Mikami, Okuda & Gilmore, 2021; Marchesan, Warner, & Byrd, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies suggest that sex hormones may influence the viral infectivity process ( Mohamed, Moulin, & Schiöth, 2021 ). However, the pathophysiology of this difference has not yet been established and it was observed that genes encoding entry factors for SARS-CoV-2 appeared similar in epithelial cells from males and females (Huang, P é rez, Kato, Mikami, Okuda & Gilmore, 2021; Marchesan, Warner, & Byrd, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, based on the included studies in this LSR, the oral lesions were negative for HHV-1, HHV-2, HHV-3, CMV, and Treponema pallidum. Nevertheless, in this sense, it is important to mention recent robust evidence that demonstrates the rich expression of SARS-CoV-2 viral entry factors in the salivary glands and epithelia of the oral mucosa, which are also sites for SARS-CoV-2 infection and replication, suggesting that the oral cavity is a hot spot for COVID-19 infection ( Huang et a., 2020 ; Huang, P é rez, Kato, Mikami, Okuda & Gilmore, 2021 ; Marchesan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 infects the oral cavity, upper respiratory tract, and large airway (Hou et al, 2020; Huang et al, 2021) prior to spread to the lower respiratory tract and the late-stage development of acute respiratory distress. Sustained replication in the oral and nasal cavities is likely a key contributor to the increased transmissibility of SARS-CoV-2 compared to other coronaviruses (Hou et al, 2020; Huang et al, 2021; Marchesan et al, 2021). For these reasons, a targeted approach for acute SARS-CoV-2 infection of the upper airway epithelia to halt progression via the oral-lung transmission axis is an attractive aim.…”
Section: Discussionmentioning
confidence: 99%
“…Iannacone's group demonstrated that inflammatory monocytes recruited to LCMV-infected LNs interacted with virus-specific B cells, confining B cell motility and decreasing B cell survival. 47 During pathogenic CHIKV-infection 56 To explore antiviral immunity in the oral mucosa, our laboratory recently adapted our skin VACV infection model to the murine labial mucosa (inner lip), which can be imaged almost noninvasively using IVM. 9,10,34 Many poxviruses replicate in the oral mucosa-the first lesions during human smallpox infection appeared in the oral mucosa rather than the skin, and smallpox patients were most infectious during the first week after the onset of symptoms as ulcerated oral mucosal lesions shed copious amounts of virus.…”
Section: Early Myeloid Control Of Viral Infectionmentioning
confidence: 99%
“…Although many medically significant viruses, including SARS‐CoV‐2, replicate in the human oropharyngeal mucosa and can be shed into the saliva, few animal models exist of acute oral mucosal viral infection, and little is known about antiviral immunity in this barrier tissue 56 . To explore antiviral immunity in the oral mucosa, our laboratory recently adapted our skin VACV infection model to the murine labial mucosa (inner lip), which can be imaged almost non‐invasively using IVM 9,10,34 .…”
Section: Visualizing the First Steps Of Viral Infection And The Innat...mentioning
confidence: 99%